FACTOR ANALYSIS OF SAVING AND INVESTMENT BEHAVIOUR OF POPULATION IN RUSSIA - Alikperova1, Natalya; Brushkova, Lyudmila; Nikolaev, Alexander; Prokhoda, Vladimir (Revista Inclusiones, 2020)
Apart from being a prerequisite for efficient operation and development of Russia's financial system, personal financial behaviour is also a factor of economic welfare. Current trends in the Russian financial market suggest that weakening welfare levels, pension reforms, low public confidence in government authorities regulating the aspects of financial behaviour create an adverse impact on the evolution of the prevalent models of financial behaviour of households. This has consolidated the research and practical relevance of, and interest in, studies concerned with the identification of the dominant saving factors, motives of transformation of savings into investment, popular attitudes to financial institutions and individual conditions and opportunities in pursuing financial strategies, particularly, saving and investment strategies.